Preharvest Salmonella Risk Contamination and the Control Strategies - Molina Alvarado, Andrea (2017)
Salmonella is present in most food production environments and can enter the food supply at any stage of food production from farm to fork. Control strategies for Salmonella include preharvest and postharvest aspects. Preharvest approach is very important because as a result of large-scale production, many animals could be infected with Salmonella serotypes during the primary production, causing human salmonellosis by consuming meat, milk, and eggs or foods containing ingredients of animal origin. The first step for prevention approaches is to determinate the source of infection; Salmonella serovars should be founded, and control strategies must be executed. Infection sources include vertical transmission, feed, pest (rodents and insects), wild birds, water, humans, manure, transportation coops, tractors or vehicles, and farm environment. Preventive and control strategies involve many factors, including hygiene, biosecurity procedures, animal feed surveillance, litter, manure and carcasses disposed, cleaning and disinfection programs, food interventions, diagnostic, and vaccination